Tempestichthys bettyae, a new genus and species of ocean sleeper (Gobiiformes, Thalasseleotrididae) from the central Coral Sea. Issue 1 (31st December 2022) - Goatley, Christopher H. R.; Tornabene, Luke
Abstract : The Thalasseleotrididae is a small family of exclusively marine gobioids. They form a sister taxon to the Gobiidae and Oxudercidae and are distinguished from most species in these families by having six branchiostegal rays and a membrane linking the hyoid arch to the first ceratobranchial. Here we use micro-CT informed morphological data and molecular phylogenetics to describe a new genus and species of thalasseleotridid discovered on a tropical oceanic coral reef in the central Coral Sea. Tempestichthys bettyae gen. et sp. nov. is the first tropical thalasseleotridid and differs from other members of the Thalasseleotrididae by having a T-shaped palatine and a distinctive shape and colouration. The three previously described thalasseleotridid species are endemic to temperate coastal waters of southern Australia and New Zealand and are all translucent brown with dorsoventrally compressed heads. However, Tempestichthys bettyae is laterally compressed with a pointed snout and is translucent white with opaque white and crimson red markings and a largely crimson iris. We discuss the unique characters of this new genus, including its distribution, form, colouration and diminutive size, and highlight the potential of there being undescribed diversity in the Thalasseleotrididae. http://zoobank.org/urn:lsid:zoobank.org:pub:3F584DD6-0B33-4E69-98A7-22D68EE1A1B8